Tingkat Kesiapan Pencari Kerja di Bekasi dalam Menghadapi Interview Kerja Online di Era Digital - Lany Melania (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The increasingly tight job competition makes job seekers, especially fresh graduates, face difficulties in getting the jobs they dream of. Thus, self-preparation for graduates who will enter the world of work is now increasingly important. This study aims to determine the level of readiness of job seekers in Bekasi City in facing online job interviews in the digital era. Along with the development of technology and changes in recruitment patterns after the COVID-19 pandemic, online job interviews have become a common selection method used by companies. However, this transition requires job seekers to have online job interview readiness, technical readiness, mental readiness, understanding of ethics. The results of the study show that the majority of job seekers in Bekasi are at a moderate level of readiness. They have sufficient access to technology, but still experience obstacles in virtual communication and mastery of certain digital platforms.